Teachers' obligations to address threats to students' well-being in Finland: educational and legal insights into preservice teachers' conceptions - Salo, Anne-Elina; Valtonen, Virve; Kajamies, Anu; Vauras, Marja (University of Aberdeen, 2026)
Students’ diverse needs and right to receive support encompass not only academic dimensions but also their broader well-being. This study aims to provide educational and legal insights into how strongly, and for what reasons, preservice class teachers (PSTs) in Finland perceive teachers to be obligated to address threats to students’ well-being. To this end, a legal perspective was incorporated into the Diverse Situations and Social Inclusion questionnaire. A mixed-method analysis was conducted (N = 114), comprising 1) Likert-scale ratings on the degree of teachers’ obligations in diverse situations threatening students’ well-being, and 2) Responses to an open-ended question about the basis of these obligations. The majority of the PSTs held that teachers were strongly obligated to address threats to well-being, particularly bullying. The most referred themes of the basis of teachers’ obligations were ‘teachers’ tasks or roles’ and ‘children’s needs’, while the themes ‘children’s rights’ and ‘written frameworks governing teachers’ work’ were more seldom mentioned. For class teacher education to cultivate PSTs’ expertise to realize children’s rights, it is vital to enhance their knowledge of these rights and written frameworks and to help them combine this knowledge with their pedagogical skills to build inclusive school communities.